"Happy Birthday" and Other Awkward Sentiments: Nixon's Social Interactions as Part of Congressional Relationship Building. Issue 2 (4th May 2019) - Hora, Jennifer
Abstract: Presidential persuasion is one of the most investigated soft-power interactions between the president and members of Congress. However, presidents are often as interested in long-term relationship building strategies that do not include an immediate favor request. This project analyzes those relationship building strategies between President Richard Nixon and members of Congress. One hundred sixty-three conversations between Nixon and members of Congress have been transcribed and analyzed. As part of an overall goal of building and maintaining interbranch relationships with members of Congress, Nixon utilized a mixture of three social goal approaches: social-support contacts, information gathering and exchange contacts, and offering material benefits.